Poly-Si thickness and temperature dependent oxide disruption induced by penetration of the interfacial oxide in (p) poly-Si/SiOx passivating contacts - Linke, Jonathan; Glatthaar, Raphael; Huster, Frank; Okker, Tobias; Möller, Sören; Hahn, Giso; Terheiden, Barbara (My University, 2022)
Passivating contacts based on polycrystalline silicon on an interfacial oxide (poly-Si/SiOx) require a fine-tuned in-diffused dopant profile at the surface of the crystalline silicon wafer. In particular, a strong dopant in-diffusion causes excessive recombination. This study contributes to reveal the yet unclear mechanism of this degradation of passivation. Boron in-diffusion from co-sputtered (p) poly-Si layers through the interfacial oxide is investigated for several layer thicknesses and plateau temperatures during the solid phase crystallization. It is shown that for higher temperatures and unexpectedly also for thicker layers the observed recombination current density increases up to a total loss of passivation, accompanied by a physical interfacial oxide disruption, which is not observed for intrinsic reference layers. This behavior is supported by simple numerical calculations. The recombination current densities are transferred into the actual surface recombination velocity which in turn reveals an exponential increase towards higher boron concentrations at the interface between the oxide and the crystalline Si base. It is concluded that rather dopant penetration of the interfacial oxide is responsible for the degradation of passivation than the actual boron concentration at the interface itself as reported before in literature.
Keywords: 530